Individual survival curves comparing subjective and observed mortality risks. (15th May 2017) - Bissonnette, Luc; Hurd, Michael D.; Michaud, Pierre‐Carl
Summary: We compare individual survival curves constructed from objective (actual mortality) and elicited subjective information (probability of survival to a given target age). We develop a methodology to estimate jointly subjective and objective individual survival curves accounting for rounding on subjective reports of perceived survival. We make use of the long follow‐up period in the Health and Retirement Study and the high quality of mortality data to estimate individual survival curves that feature both observed and unobserved heterogeneity. This allows us to compare objective and subjective estimates of remaining life expectancy for various groups and compare welfare effects of objective and subjective mortality risk using the life cycle model of consumption. We find that subjective and objective hazards are not the same. The median welfare loss from misperceptions of mortality risk when annuities are not available is 7% of current wealth at age 65 whereas more than 25% of respondents have losses larger than 60% of wealth. When annuities are available and exogenously given, the welfare loss is substantially lower.